Alteration In Liver Function Induced by Toluene Subcutaneous Administration in Rabbits: Perubahan Fungsi Hati yang Diinduksi oleh Pemberian Toluena Subkutan pada Kelinci - Ali, Wasfi Dhahir Abid (Universitas Muhammadiyah Sidoarjo, 2024)
The current study aims to determine the effect of the dye on the liver morphology of male rabbits. The coloring substance is considered toxic when exposed to it for periods and remains inside the body. The study’s results showed a significant effect on liver enzymes, thus affecting liver histology. The liver enzymes AST, ALP, and ALT increased, 38.514 +0.99 44.770 +0.105, and 50.758 + 0.882, respectively. These are considered indicators of liver damage, which is reflected in its functions Highlights: Dye exposure significantly affects liver morphology in male rabbits. Elevated AST, ALP, and ALT indicate liver damage. Histological changes reflect impaired liver function. Keywords: toluene, liver, kidney, AST, ALP, ALT, and Liver tissue